Resiliensi Psikologis Perempuan yang Mengalami Kekerasan dalam Berpacaran (Studi Kasus pada Mahasiswa Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember) - Syaidah; Cholilah, Indah Roziah (Fakultas Dakwah UIN KHAS Jember, 2023)
Students who engage in romantic relationships with hopes of finding motivation from their partners often find themselves subjected to various forms of violence, including psychological, physical, economic, and sexual abuse. However, students who experience such violence have the ability to rise from adversity, a capacity known as resilience. The aim of this research is to explore the types of violence experienced by students at UIN Kiai Haji Achmad Siddiq in Jember during romantic relationships and to understand the psychological resilience of women who experience violence in such relationships. This study employs a descriptive qualitative approach to analyze the psychological resilience of women following experiences of violence in romantic relationships. Subjects were selected through purposive sampling, targeting female students at UIN Kiai Haji Achmad Siddiq who have experienced violence during dating. Data collection techniques include semi-structured interviews, participatory observation, and documentation. The study reveals that violence experienced by students in romantic relationships includes psychological, physical, economic, and sexual violence, such as coercion into sexual activities. Psychological resilience among women experiencing violence in romantic relationships is demonstrated through behaviors such as emotional regulation, impulse control, optimism, empathy, engaging in various activities, self-efficacy, and reaching out for support.